The Role of Labor Protection in Production - Moydinova, Y.G.; Tairov, Sh. M. (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses the importance of organizing labor protection at the enterprise, their impact on the final result of production activities, a brief comparative analysis with foreign experience is carried out. It also examines the main factors affecting the safety of workers, and suggests ways to solve problems arising in the field of labor protection.